Preclinical validation of a live attenuated dermotropic Leishmania vaccine against vector transmitted fatal visceral leishmaniasis - Subir Karmakar (Nature Portfolio, 2021)
Karmakar et al produced a dermotropic, live attenuated centrin gene-deleted Leishmania major (LmCen −/− ) vaccine against Visceral Leishmaniasis (VL). They demonstrated in hamsters that a single intradermal injection confers robust and durable protection against lethal VL that is transmitted naturally via bites of L. donovani-infected sand flies.